The Effect of Organizational Trust, Brand Image, and Religiosity on Donation Decision Making with Information Quality as an Intervening Variable at the Integrated Village Service Foundation - Lendy Tampi; Hilarius Bambang Winarko (UNIVED Press, 2024)
This research aims to measure the extent to which organizational trust, brand image, and religiosity influence donation decisions at the Integrated Village Service Foundation (PESAT), with information quality as an intervening variable. This study utilizes a quantitative approach and falls under the explanatory research type. The research sample consists of 115 PESAT donors selected using quota sampling. Data obtained are analyzed using Partial Least Squares (PLS) analysis techniques through SmartPLS software and SPSS 23. The research results indicate that organizational trust and information quality significantly influence donation decisions, while brand image and religiosity do not have a significant impact on donation decisions. Other findings show that the brand image and religiosity variables significantly affect information quality, while organizational trust does not have a significant impact on information quality. Regarding indirect influence, it is found that brand image significantly influences donation decisions through information quality, and religiosity significantly influences donation decisions through information quality, whereas organizational trust does not significantly influence donation decisions through information quality. Simultaneously, organizational trust, brand image, and religiosity collectively influence donation decisions.